The Influence of Performance Assessment System and Self-Efficacy on Organizational Performance with Work Motivation as an Intervening Variable : A Study at the Malang Raya Primary Tax Service Office - Rizki Yudi Prakoso; Muryati Muryati; Muchlis Mas'ud (Brilliant International Journal Of Management And Tourism, 2025)
The purpose of this study is to analyze and empirically test the effect of performance appraisal system and self-efficacy on organizational performance with work motivation as an intervening variable. This study was designed to test and explain the causal relationship between variables, both directly and indirectly. The population in this study were all account representatives at the Malang Raya Pratama Tax Service Office with a total of 120 people. The determination of the number of samples for this study used the Slovin formula, which was 92 people. The determination of sampling was based on proportionate random sampling. The inferential statistical method used to analyze this study was Partial Least Square and using SmartPLS version 4. The results showed that the performance appraisal system was unable to play a role in improving organizational performance. Self-efficacy was able to play a role in improving organizational performance. Work motivation was able to play a role in improving organizational performance. The performance appraisal system was able to play a role in improving work motivation. Self-efficacy was able to play a role in improving work motivation. Work motivation was able to mediate the relationship between the performance appraisal system and organizational performance. Work motivation can mediate the relationship between self-efficacy and organizational performance.